1983
DOI: 10.1002/mpo.2950110413
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma of the larynx treated by laser surgery combined with radiotherapy and chemotherapy

Abstract: The case of a 6-year-old boy with rhabdomyosarcoma of the larynx, treated by laser surgery combined with external radiotherapy and chemotherapy, is presented. Using this treatment modality, cure was affected without comprising laryngeal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Seventeen case reports of laryngeal embryonal rhabdomyosarcoma were identified, and a summary of the pertinent aspects of treatment and outcome are summarised in Table I. Here, we present the first well-documented case of subglottic embryonal 9 6 y, M Arytenoid, posterior commissure Local excision, RT, CT No evidence of disease (2 y) Diehn et al 10 1 y, F Not reported None Died of disease (6 mth) Diehn et al 10 16 y, M Aryepiglottic fold, arytenoid, posterior commissure…”
Section: Discussionmentioning
confidence: 97%
“…Seventeen case reports of laryngeal embryonal rhabdomyosarcoma were identified, and a summary of the pertinent aspects of treatment and outcome are summarised in Table I. Here, we present the first well-documented case of subglottic embryonal 9 6 y, M Arytenoid, posterior commissure Local excision, RT, CT No evidence of disease (2 y) Diehn et al 10 1 y, F Not reported None Died of disease (6 mth) Diehn et al 10 16 y, M Aryepiglottic fold, arytenoid, posterior commissure…”
Section: Discussionmentioning
confidence: 97%
“…It accounts for 41% of all rhabdomyosarcomas found in the head and neck regions. 2 Only about 8% of head and neck rhabdomyosarcomas involve the middle ear and mastoid; it is a rare condition. Rhabdomyosarcomas in patients older than 20 years are relatively uncommon; they are rare after the age of 45.…”
Section: Discussionmentioning
confidence: 99%
“…Rhabdomyosarcoma is the most common soft tissue sarcoma occurring in children. It accounts for 41% of all rhabdomyosarcomas found in the head and neck regions 2 . Only about 8% of head and neck rhabdomyosarcomas involve the middle ear and mastoid; it is a rare condition.…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for 53 per cent of all softtissue sarcomas and 13 per cent of all malignant solid tumours in this age group (Green and Jaffe, 1981). Fourty-one per cent of all rhabdomyosarcomas in children are found in the head and neck region (Kedar et al 1983). Middle ear and mastoid involvement accounts for about 8 per cent of head and neck rhabdomyosarcomas (Sutow et al, 1982).…”
Section: Incidencementioning
confidence: 99%